2011
DOI: 10.1007/s00382-011-1132-z
|View full text |Cite
|
Sign up to set email alerts
|

Potential decadal predictability and its sensitivity to sea ice albedo parameterization in a global coupled model

Abstract: Decadal prediction is one focus of the upcoming 5th IPCC Assessment report. To be able to interpret the results and to further improve the decadal predictions it is important to investigate the potential predictability in the participating climate models. This study analyzes the upper limit of climate predictability on decadal time scales and its dependency on sea ice albedo parameterization by performing two perfect ensemble experiments with the global coupled climate model EC-Earth. In the first experiment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 50 publications
1
37
0
Order By: Relevance
“…volume with respect to that of sea ice concentration (i.e. area or extent), found in all seasonal to interannual predictability studies seems to disappear when considering longer time scales, as shown by the very weak predictability of SIV, in contrast to the highly predictable sea ice extent (SIE) found on decadal means by Koenigk et al (2012).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…volume with respect to that of sea ice concentration (i.e. area or extent), found in all seasonal to interannual predictability studies seems to disappear when considering longer time scales, as shown by the very weak predictability of SIV, in contrast to the highly predictable sea ice extent (SIE) found on decadal means by Koenigk et al (2012).…”
Section: Introductionmentioning
confidence: 88%
“…Longer-term Arctic sea ice predictability has been investigated using perfect model assumption, in which Global Climate Models (GCMs) ensemble integrations are initialized from a reference model integration (Koenigk and Mikolajewicz 2009;Koenigk et al 2012;Tietsche et al 2013). These studies examined the upper limit of initial-value predictability and its sensitivity to the Arctic sea ice mean state , which is an important issue in the observed rapidly changing Arctic sea ice conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sector (Koenigk et al, 2012), due to a strong correlation with the meridional overturning circulation in the North Atlantic Ocean. Such results suggest that the outlook is positive for future climate prediction in the Arctic.…”
Section: R Döscher Et Al: Recent Advances In Understanding the Arctmentioning
confidence: 99%
“…Koenigk et al (2012) have indicated that the increasing ocean heat transport strongly contributes to the reduced sea ice cover in the Barents and Kara Sea region, and thus hypothetically also contributes to the Arctic temperature amplification of the global climate warming (see Sect. 2.1).…”
Section: Links Between Ocean Heat Transport and Sea Ice Meltmentioning
confidence: 99%